2011
DOI: 10.1155/2011/830320
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride-Sensitive Sodium Channels and Pulmonary Edema

Abstract: The development of pulmonary edema can be considered as a combination of alveolar flooding via increased fluid filtration, impaired alveolar-capillary barrier integrity, and disturbed resolution due to decreased alveolar fluid clearance. An important mechanism regulating alveolar fluid clearance is sodium transport across the alveolar epithelium. Transepithelial sodium transport is largely dependent on the activity of sodium channels in alveolar epithelial cells. This paper describes how sodium channels contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 78 publications
1
40
0
Order By: Relevance
“…ENaC is composed of four homologous subunits (a, b, g, and d), each comprising a large extracellular loop lying between two transmembrane domains flanked by short cytoplasmic amino and carboxyl termini (Canessa et al, 1994a;McDonald et al, 1994;Snyder et al, 1994;Althaus et al, 2011). Posttranslational modification of ENaC involves proteolytic cleavage of the a and g subunits (Hughey et al, 2003;Kleyman et al, 2009;Gaillard et al, 2010) and N-glycosylation of the a, b, and g subunits Adams et al, 1997;Hughey et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ENaC is composed of four homologous subunits (a, b, g, and d), each comprising a large extracellular loop lying between two transmembrane domains flanked by short cytoplasmic amino and carboxyl termini (Canessa et al, 1994a;McDonald et al, 1994;Snyder et al, 1994;Althaus et al, 2011). Posttranslational modification of ENaC involves proteolytic cleavage of the a and g subunits (Hughey et al, 2003;Kleyman et al, 2009;Gaillard et al, 2010) and N-glycosylation of the a, b, and g subunits Adams et al, 1997;Hughey et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…ENaC is a member of the degenerin family of nonvoltage-gated ion channels. In epithelial tissues, the channel is composed of four homologous subunits (a, b, g, d) with 30-40% identity in their amino acid sequence (Canessa et al, 1994b;Althaus et al, 2011). It was shown that expression of a-ENaC alone or in combination with either b or g-ENaC is sufficient to make a conducting channel.…”
mentioning
confidence: 99%
“…In the distal lung, sodium and liquid absorption across the alveolar epithelium maintain a thin liquid layer, which is necessary for diffusion of O 2 /CO 2 . Impaired sodium absorption can lead to liquid accumulation in the lung and the formation of pulmonary edema (4). Understanding the physiological and pathophysiological regulation of ENaC-mediated sodium absorption is, thus, an important topic in lung physiology.…”
mentioning
confidence: 99%
“…Additional ENaC inhibitors, including P-1037 (NCT02343445) and GS-9411 (NCT00999531), are being developed, and investigations into molecular regulators of ENaC function uncovered an ENaC modulator that showed inhibition of the protein diglyceride kinase 1 that decreased ENaC activity and normalized sodium and fluid absorption in CF airways. Excessive blocking of ENaC function can lead to unwanted consequences, including fluid accumulation in the lungs and subsequent pulmonary edema (49), and thus any potential future therapeutic agent targeting the ENaC sodium channel to normalize airway surface liquid needs to address this issue.…”
Section: Non-cftr-based Therapeutic Approachesmentioning
confidence: 99%